SISTEM INFORMASI PERHITUNGAN TUNJANGAN PEGAWAI DAN GAJI HONORER BERBASIS WEBSITE PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN KUPANG - Amalo, Nehemia Daniel; Katemba, Petrus (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2021)
The Office of Investment and Integrated Services of the One Door Kupang District still uses the system manually in the process of calculating the additional allowances for employee income and the salaries of honorary staff. The weakness of the existing system is that the system is inefficient, takes a lot of time in the process of managing employee benefits and payroll honorary staff based on employee absence. So this research aims to design a model of Information Systems for Employee Benefits and Employee Payroll Calculation based on the Website at the Investment and Integrated Services One Door Service (DPMPTSP), as well as facilitate in managing data and employee benefits that are precise and accurate. The research method used is the method of literature and field. The calculation information system using the Personal Home Page (PHP) programming language and as its database using MySql thus can be implemented an information system for calculating employee benefits and payroll honorary staff at the Office of Investment and Integrated Services One Door Kupang District